Forms and Method of Messenger Muhammad PBUH Ijtihad | صور اجتهاد الرسول صلى الله عليه وسلم ومنهجه - Muhammada Waidus Simbo (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2011)
This research gives a view about Ijtihad of Prophet Muhammad (Peace be Upon Him),and his methodology of ijtihad. The research has two topics: first, ijtihad of ProphetMuhammad PBUH, which includes the ijtihad verbally (Qauliyah), practically (Fi’liyah),and decision (Taqririyah). Seconds, Prophet Muhammad’s PBUH method in ijtihad andanalogy. The research refers to the classical books, the kutub as sittah (six hadis books). Inthis research the writer tries to make tahqiq and takhrij of all hadis used. He also explainsbreafly the biography of the rawi.